A new classification of Cyperaceae (Poales) supported by phylogenomic data. Issue 4 (25th June 2021) - Larridon, Isabel; Zuntini, Alexandre R.; Léveillé‐Bourret, Étienne; Barrett, Russell L.; Starr, Julian R.; Muasya, A. Muthama; Villaverde, Tamara; Bauters, Kenneth; Brewer, Grace E.; Bruhl, Jeremy J.; Costa, Suzana M.; Elliott, Tammy L.; et al.
Abstract: Cyperaceae (sedges) are the third largest monocot family and are of considerable economic and ecological importance. Sedges represent an ideal model family to study evolutionary biology due to their species richness, global distribution, large discrepancies in lineage diversity, broad range of ecological preferences, and adaptations including multiple origins of C4 photosynthesis and holocentric chromosomes. Goetghebeur′s seminal work on Cyperaceae published in 1998 provided the most recent complete classification at tribal and generic level, based on a morphological study of Cyperaceae inflorescence, spikelet, flower, and embryo characters, plus anatomical and other information. Since then, several family‐level molecular phylogenetic studies using Sanger sequence data have been published. Here, more than 20 years after the last comprehensive classification of the family, we present the first family‐wide phylogenomic study of Cyperaceae based on targeted sequencing using the Angiosperms353 probe kit sampling 311 accessions. In addition, 62 accessions available from GenBank were mined for overlapping reads and included in the phylogenomic analyses. Informed by this backbone phylogeny, a new classification for the family at the tribal, subtribal, and generic levels is proposed. The majority of previously recognized suprageneric groups are supported, and for the first time, we establish support for tribe Cryptangieae as a clade including the genus Koyamaea . We provide a taxonomic treatment including identification keys and diagnoses for the 2 subfamilies, 24 tribes, and 10 subtribes, and basic information on the 95 genera. The classification includes five new subtribes in tribe Schoeneae: Anthelepidinae, Caustiinae, Gymnoschoeninae, Lepidospermatinae, and Oreobolinae.